The Srategic Role of Muhammadiyah: Pluralism, Tolerance and Socialism in Indonesia - Masrukhi Masrukhi; Supaphorn Akkapin (PT. Multidisciplinary Press Indonesia, 2024)
Indonesia is the country with the fourth largest population in the world. Where Indonesia has multi-culture, multi-ethnicity and multi-language. Muhammadiyah has a role in the development of the Indonesian nation, especially in the fields of social and pluralism. In the social sector, Muhammadiyah plays a very strategic role, including providing health facilities and education. Muhammadiyah views tolerance as a form of universal human brotherhood and mutual respect, where pluralism and tolerance are efforts to resolve various national problems. Muhammadiyah agrees with the philosophy of the Indonesian nation; Even though we have different ethnicities and religions, we are still one nation.